A dual radiolabelling approach for tracking metal complexes: investigating the speciation of copper bis(thiosemicarbazonates) in vitro and in vivo1. Issue 5 (13th May 2015) - Hueting, Rebekka; Kersemans, Veerle; Tredwell, Matthew; Cornelissen, Bart; Christlieb, Martin; Gee, Antony D.; Passchier, Jan; Smart, Sean C.; Gouverneur, Véronique; Muschel, Ruth J.; Dilworth, Jonathan R.
<x xml:space="preserve">Abstract</x> A pair of [123I]/[64Cu]-copper bis(thiosemicarbazonates), radiolabelled at either the metal or at the ligand, was used to examine the roles of the copper metal and the ligand in the in vitro and in vivo behaviour of this class of hypoxia PET imaging agent.